QOLP-13. IMPACT OF CANNABIS USE ON QUALITY OF LIFE IN PATIENTS WITH CENTRAL NERVOUS SYSTEM TUMORS. (11th November 2019) - Rodriguez Almaraz, Eduardo; Butowski, Nicholas; Chang, Susan; Ann Oberheim-Bush, Nancy; Clarke, Jennifer; Taylor, Jennie; Buerki, Robin; Berger, Mitchel
Abstract: BACKGROUND: Nearly 80, 000 new cases of primary brain tumors are expected to be diagnosed this year, 32% of CNS tumors are malignant. Anecdotally, patients who report use of cannabis, frequently describe higher quality of life scores (QOL) in standardized instruments. However, the lack of available tools that allow systematic documentation of cannabis use results in a barrier to accurately assess efficacy, potential benefits and risks. METHODS: We conducted a single center, observational study: patients with primary brain tumors answered a previously validated instrument to explore cannabis use. QOL was assessed using the instruments from the European Organisation for Research and Treatment of Cancer: QLQ-C30 and its complementary module BN-20 as well as the EuroQol instrument EQ-5D-5L. Eligible participants were identified as cannabis users or non-users, completing the instruments in a self-administered fashion. RESULTS: To date, 51 patients who signed informed consent were enrolled and answered the questionnaires, mean age was 51 (SD 12.95) years, 34 were male, 30 were considered active cannabis users (66.6% males and 33.3% females). The mean global health score in the QLQ-C30 instrument was 68.4 (SD: 20.7) among cannabis users and 82.2 (SD: 17.5) among non-users. The mean difference in QOL scores between users and non-users was 13.8 (95%CI: 2.8, 24.8; p=0.01). In contrast the difference between cannabis users and non-users in QOL index in the EQ-5D-5L instrument was 0.13 (95% CI: 0.06, 0.2; p=0.001). Among cannabis users, patients perceive their symptoms as moderate before using cannabis and mild after using cannabis (p >0.001) CONCLUSIONS: In our analysis, patients who use cannabis reported, on average, lower QOL scores. Potentially, sicker patients resort to cannabis to improve their symptoms and ultimately quality of life. The perception of patients is that cannabis usage improves overall quality of life. Findings provide support to perform prospective studies.